Unemployment and economic and social impacts in Tartous - Alrbdawy, Kasem; Maia, Loubana (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Unemployment in Tartous Governorate is economic problem - social suffered by the population, represented in inability of the younger categories find jobs commensurate with educational qualifications especially the Supreme (average Institute and the academics) , Unemployment is a waste of human resources available that lacking use, and take advantage of them positively reflected on the life of the population, individuals and society, and the most important results: Decline in the unemployment rate between /2004-2010/ compared with Its rates between /1994-2004/, but it remained higher than the level of Syria, with higher rates for females compare with males, in addition to the high unemployment rate for ages /15-24/, which It is the most active category in the community, compared with ages /25 years/ and more , and the rates of females is higher than males, It was also noted the high unemployment rate for higher education degree holders, especially for females between /2001-2010/ compared with the educational certificates least, which dropped In /2010/ compared with /2001/, and its impact on social and economic life on Population